Study of printed electronics - Low, Kim Huat. (2009)
Printed electronics are a relatively new technology that has attracted key interests in recent years and has a huge potential market that could hit $300 billion dollars. This technique enables the cutting down of manufacturing cost of semiconductor and better utilization of raw material such as silicon reduces space. There has been extensive research in materials that could be used for printed electronics and improvement in the technique to yield better quality electronic devices. In this project, the micro inkjet printing technique is explored. Micro inkjet printing and sol gel technique are used to fabricate SiO2 film and ZnO film. The results using the two techniques compared and studied. Besides, observations of the printing technique are also made such as the process of the technique and its limitations. Parameters such as film thickness, current voltage characteristics, and capacitance voltage characteristics are measured by various equipment. The results are analyzed and key relationship trends from the results are deduced. From the printing technique, one could deduce that the film thickness and film width are inversely proportional to the pitch size of the droplet. Also, printing exhibits more consistent controlling of film thickness compared to sol gel technique. The differences in the current voltage characteristics results are mainly due to the difference in film thickness rather than the technique used. Lastly, capacitance voltage characteristics show that printing technique produce better quality film and allow more accurate measurement of the dielectric constant. Also, printed ZnO film has shown interesting property in which breakdown voltage only occurs at the negative potential. The project still has many unexplored boundaries. Surface porosity and uniformity could be investigated. Current voltage characteristics could be studied on device with similar film thickness instead. Also, ZnO film could be further examined.